2021
DOI: 10.1021/acsaem.1c02066
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Rutile/Anatase Micro-Heterophase Junction Photocatalyst from Anatase by Liquid Nitrogen Quenching Method

Abstract: Heterophase junction composite semiconductors have been documented to exhibit better photocatalytic activity than the corresponding single-phase semiconductors for chemical reactions such as the hydrogen evolution and the degradation of pollutants. However, how to further improve the photocatalytic activity of these materials is a great challenge from the perspective of theory and practice. Herein, we report the synthesis of the rutile/anatase micro-heterophase junction from nanoscale anatase TiO 2 by a rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
(143 reference statements)
0
12
0
Order By: Relevance
“…In the presence of oxygen, the signals assigned to oxygen vacancy (g = 2.003) and Ti 3+ centers in the anatase TiO2 (g = 1.990) are identified on the Pt1/WO3-TiO2 in the dark (Fig. S11) 33,42,43 . Upon the light illumination, the additional EPR signals (gxx = 2.017, gyy = 2.012, gzz = 2.002) appear, which can be allocated to the surface trapped hole centers O3…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of oxygen, the signals assigned to oxygen vacancy (g = 2.003) and Ti 3+ centers in the anatase TiO2 (g = 1.990) are identified on the Pt1/WO3-TiO2 in the dark (Fig. S11) 33,42,43 . Upon the light illumination, the additional EPR signals (gxx = 2.017, gyy = 2.012, gzz = 2.002) appear, which can be allocated to the surface trapped hole centers O3…”
Section: Resultsmentioning
confidence: 99%
“…CO adsorption in-situ infrared experiment, isotope tracing experiment and quantitative calculation showed that this unique Pt-TiO 2 interface structure enabled the CO adsorbed on Pt to be oxidized by adjacent holes. Wang et al 18 also reported that rutile/anatase heterophase junctions were prepared by rapid heat treatment combined with liquid nitrogen quenching of nanoscale anatase TiO 2 (Fig. 9(E)).…”
Section: Interface Defectsmentioning
confidence: 93%
“…13,14 By constructing a heterojunction structure, a built-in electric field is generated at the heterojunction interfaces, which can spontaneously orient and expedite the transfer of photogenerated electrons from one semiconductor to the other and the transfer of holes toward the opposite direction and also could greatly reduce the recombination of photogenerated electrons and holes in the transfer process from bulk towards the surface. A good deal of heterocomposites, including those with p–n heterojunction structures, 13 Z-scheme structures, 15,16 Schottky junction structures, 17 and heterophase junction structures, 18,19 have been reported as active photocatalysts for various energy and environment reactions. Many reviews have summarized heterojunction photocatalysts and their applications.…”
Section: Introductionmentioning
confidence: 99%
“…From the XRD test results in Figure 1a, the typical anatase peak pattern of TiO 2 can be seen; the peaks appearing at 2θ = 25.347 [30,31]. When compared to other peaks, the intensity of the peak at 25.347 • is the highest, indicating that the corresponding (101) crystal plane is the most exposed.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 96%